Epidemiology of pneumococcal infections in hospitalised adult patients in Lebanon with a highlight on non-invasive disease - Rima Moghnieh; Lyn Awad; Dania Abdallah; Rahil Sleiman; Tamima Jisr; Hani Tamim; Mona Al Helou; Ahmad Ibrahim; Anas Mugharbil; Nabila Droubi; Lina Reslan; Ghassan M Matar; et al. (Journal of Infection in Developing Countries)
Introduction: Streptococcus pneumoniae causes a wide range of infections classified as invasive and non-invasive pneumococcal disease (non-IPD).